Performance of Anthurium (Anthurium anderanum Lindl) cultivars under hill zone of Karnataka - S K Nataraj (Society for Promotion of Horticulture - Indian Institute of Horticultural Research, 2019)
An investigation was carried out at experimental block, College of Horticulture, Mudigere. Tropical recorded maximum LAI 2.83, and had maximum plant height, number of leaves, leaf area and Leaf area Index. Cultivar Crinkle Red recorded maximum number of flowers per plant per year (13.14), which was on par with Tropical (11.77), Cheers (10.60) and Fire (10.25). Cultivar Midori recorded maximum vase life (35.00 days) followed by Tropical (33.33 days) and it was on par with Fire (32.22 days). Cultivar Midori recorded maximum vase life (35.00 days), followed by Tropical (33.33 days) and it was on par with Fire (32.22 days) and highest B:C ratio is recorded in cultivar Tropical (1.83) and it was least in Fantacia (1.13) .